Taxonomic revision of the stone geckos (Squamata: Diplodactylidae: Diplodactylus) of southern Australia - Hutchinson, Mark N.; Doughty, Paul; Oliver, Paul M. (Zootaxa, 2009)
The stone geckos of the Diplodactylus vittatus species-group are robust terrestrial geckos, mainly distributed through the southern half of Australia. Recent molecular analyses indicate that the current taxonomy significantly under-represents the true diversity in this group. Here we assess the morphological variation in the currently recognized species D. vittatus and D. granariensis, including the subspecies D. g. rex. We redescribe D. vittatus and D. granariensis, resurrect D. furcosus from the synonymy of D. vittatus and describe D. calcicolus sp. nov. and D. wiru sp. nov. from semiarid habitats in western and southern Australia. Other than D. g. rex, most taxa are very similar for such characters as scalation, body and tail shape and size, but colour patterns show species-specific modal conditions, and the largely allopatric distributions mean that most areas support only one or two species which can be distinguished through a combination of characters. Further genetic data is required to resolve the systematic status and geographic distribution of additional deeply divergent genetic lineages in eastern Australia.